Efektifitas Pola Promosi On-Line Dalam Upaya Mempertahankan Penjualan Produk Clinique Pada Masa Pandemic Covid-19 - Iman Chaerudin; Atikah Atikah (Journal of Economics and Business UBS, 2022)
COVID-19 has swept the world in a matter of months, endangering lives, damaging businesses and triggering a global economic downturn. Restrictions on physical distancing and staying at home have forced all segments of consumers to shop differently especially consumer goods including home entertainment. Currently, cosmetics have become a basic need for some women & even adult men to clean & beautify themselves, so this online shopping reseach includes shopping for beauty products for adult women & men who in their daily life cannot be separated from cosmetics. In the Industrial Era 4.0 where the Internet is the main tool to regulate production and non-production activities, encouraging changes in people's behavior. One of them is the pattern of promotion & online shopping. The condition of hypercompetition & changes in on-line shopping behavior is the purpose of this study to determine the effectiveness of on-line promotions specifically for Clinique brand cosmetic products. Using quantitative analysis techniques, it turns out that 9 out of 10 respondents do online shopping to meet their daily needs by using the internet network to stay at home. Digital promotion, personal care and publicity using mobile, computer/laptop communication tools and personal selling were able to maintain sales of 60% of the sales target.